Empowering parents of children with disabilities: assessing the impact of a child sexual abuse psychoeducation program in Türkiye. - Kaçan, Havva; Sakız, Halis (International Journal of Developmental Disabilities, 2026)
Child sexual abuse (CSA) is a pervasive problem that can have detrimental effects on the physical and mental health of children, as well as their families. Parents of children with disabilities (CWD) may face additional challenges in protecting their children from sexual abuse. This study aimed to examine the effects of a CSA psychoeducation program for parents of CWD. The program was designed to increase parental knowledge and attitudes towards CSA and prevention strategies, as well as to decrease parents' anxiety regarding the topic. A total of 93 parents of CWD participated in the study, with 45 being randomly assigned to the experimental group and 48 to the control group. The findings suggest that the CSA psychoeducation program was effective in increasing parental knowledge and attitudes towards CSA prevention strategies. The experimental group scored significantly higher than the control group in all domains of the Child sexual abuse knowledge/attitude scale for parents. Additionally, the program was effective in reducing parents' anxiety. This highlights the need for such programs to be implemented in schools and other community settings to increase parental awareness and prevent CSA.